A survey on the sterilization techniques employed by selected dental private practioners in Ermita, Manila - Guzman, Barbara Pamela A.; Marana, Ma. Rhea A.; de Castro, Elizabeth (Adviser).
A survey of sterilization techniques was taken among a sample of 33 private dentists practicing in Ermita, Manila. it was found out that boiling is by far the most popular sterilization technique but only a small fraction of the sample boil for at least 30 minutes, as recommended by the World Health Organization; isopropyl alcohol is greatly favored by the respondents as a wiping agent for handpieces and about one-third of the sample do not sterilize their handpieces at all. A profile of the respondents reveal that private dental practitioners in Ermita are mostly young professionals 34 years old or younger; employ one auxiliary each and attend conventions and seminars to earn units for continuing education.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Infection Control, Dental -- Methods